Serious Game model for dyslexic children - Zeeshan Bhatti; Naila Shabbir (Sukkur IBA Journal of Computing and Mathematical Sciences, 2022)
Dyslexia is a hidden neurological disorder in which children suffering with weak phonological awareness and that affects his/her poor academic records. A dyslexic child is quit intellectual and interestingly good in different fields of life but weak in language-based learning. They feel difficult to identify similar face letters which led them to misspell and wrong pronunciation. Serious gaming and cognitive learning through assistive applications emerged in the 21st century. Numerous serious gaming applications are developed to combat the issue for effective cognitive learning for dyslexic children and the degree of success is vary due to the lack of standard postulates to design and develop a novel system for such young hearts with pure entertainment that cure their cognitive weakness. It‟s quite difficult to claim that a serious game meets the standard learning pedagogy for a special group of users. This research paper proposed a serious gaming model for dyslexic children to pursue the issue of standard rules for serious gaming applications for developers to achieve effective learning outcomes.